The Effect of Communication in Emergency Department Isolation Rooms Using Smart Glasses: A Mixed‐Methods Study. - Park, Soyoung; Lee, Hyeongsuk (Journal of Clinical Nursing (John Wiley & Sons, Inc.), 2025)
Aim: To assess the effectiveness of using smart glasses to facilitate communication among nurses inside and outside the emergency department. Design: Complementary mixed‐methods study with a one‐group pretest‐posttest design. Methods: Thirty emergency nurses participated in surveys on demographics, digital literacy, and communication clarity before and after using smart glasses. Qualitative interviews explored user experiences. Results: Smart glasses improved communication clarity. No significant correlation was found between demographics or clinical experience and communication clarity. Qualitative analysis identified five facilitating factors—reduced nursing workload, enhanced patient care, improved efficiency, reliable support, and professional feel—and five barriers—user interface issues, surveillance burden, communication errors, technology‐integration limitations, and ethical/patient privacy concerns. Conclusion: Smart glasses improved communication in emergency isolation rooms, potentially enhancing patient safety and reducing treatment delays. Addressing usability and ethical concerns is key for successful integration. Implications for the Profession and/or Patient Care: Smart glasses offer significant potential to enhance communication. To maximise their benefits, it is crucial to address challenges such as the added stress on novice nurses, potential increases in workload, and ethical concerns regarding patient privacy. Providing comprehensive training and refining the technology will help to reduce user burden and ensure robust data security, ultimately improving patient care and supporting nursing staff in high‐stress environments. Impact: Smart glasses can improve communication among emergency nurses, especially in isolation rooms, by reducing treatment delays and enhancing collaboration, thus improving patient safety. Reporting Method: TREND (Nonrandomised evaluations of behavioural and public health interventions). Patient or Public Contribution: Emergency nurses' feedback was integral to evaluating the usability and effectiveness of smart glasses.